Gut and Lung Microbiota in Preterm Infants: Immunological Modulation and Implication in Neonatal Outcomes - Tirone, Chiara; Pezza, Lucilla; Paladini, Angela; Tana, Milena; Aurilia, Claudia; Lio, Alessandra; D'Ippolito, Silvia; Tersigni, Chiara; Posteraro, Brunella; Sanguinetti, Maurizio; Di Simone, Nicoletta; Vento, Giovanni (Frontiers in Immunology, 2019)
In recent years, the interest for the study of the origins of intestinal dysbiosis in preterm infant is increased as aberrant gastrointestinal colonization has been associated with a higher risk for postnatal sepsis, necrotizing enterocolitis (NEC) and growth impairment in this population of newborns. An apparent connection exists also between the development of gut and lung microbiome (gut-lung axis), and more data show as a gut-brain cross talking mediated by an inflammatory milieu, may impact to the immunity system and influence neonatal outcomes. A revision of the studies which examined gut and lung microbiota in preterm infants and a qualitative analysis of data about characteristic patterns and related outcomes in terms of risk of growing impairment, Necrotizing Enterocolitis (NEC), brain development, Bronchopulmonary Dysplasia (BPD) and sepsis has been performed. Microbiota shows a key role in the establishment of the gut barrier and many data suggest its immune-modulator role. A connection between the development of the gut and lung microbiome (gut-lung axis), able to lead to abnormal inflammatory responses, with the pathogenesis of BPD has been proposed. Dysbiosis and the gut predominance of facultative anaerobes appear to be crucial to the pathogenesis and subsequently to the prevention of such diseases.